New genus and species of the weevils of the tribe Blosyrini closely related to Stiltoblosyrus Davidian, 2020 (Coleoptera: Curculionidae: Entiminae) - G.E. Davidian (Кавказский энтомологический бюллетень, 2022)
A new weevil genus Kabakiellus Davidian, gen. n. (Entiminae: Blosyrini) is described from the western part of Yunnan Province in China. It is characterized in the following features: the rostrum is slightly or moderately narrowed apically; antennal scrobes are clearly visible in dorsal view; the pronotum is widest at middle, evenly rounded laterally; apical tubercles at the 5-th elytral interstriae are not protruding beyond the apex of elytra; hind tibiae of the male are with the distinct elongated or flattened process at the place of the mucro; the armament of internal sac is with numerous spinules and spicules and two sclerites at the level of the base of the penis. The new genus is well distinguished from the most genera of the tribe Blosyrini in presence of the process at the place of the mucro on the hind tibiae of the male, as well as the absence of anterior sclerites, endophallic rods and clusters of spinules in the armament of the endophallus. The new genus is similar to Stiltoblosyrus Davidian, 2020 in structure of hind tibiae of the male and the reduced armament of endophallus, from which differs in the pronotum evenly rounded laterally and in presence two posterior sclerites of the endophallus. Two new species including K. fugongicus sp. n. (type species), K. alpicolus sp. n. are described from Yunnan Province of China. Stiltoblosyrus lisu Davidian, 2020 is transferred to the genus Kabakiellus (K. lisu, comb. n.). Kabakiellus fugongicus sp. n. is the most similar to K. lisu and easily differs in the structure of straight hind tibiae of the male with more shortened and dorso-ventrally flattened process at the place of the mucro. Kabakiellus alpicola sp. n. differs from congeners in having the smaller body size and in the structure of the hind tibiae of the male with ovate flattened process at the place of the mucro. A key to three species of the genus Kabakiellus Davidian, gen. n. is given